CONSUMERS’ GREEN PURCHASE INTENTIONS: ENVIRONMENTAL KNOWLEDGE AND GREEN ADVERTISING INTO GREEN ENVIRONMENTAL ATTITUDES - Rennyta Yusiana; Arry Widodo; Agus Maolana Hidayat (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
Objectives: One of the causes of environmental damage or environmental pollution is the existence of conventional factory activities and waste that is not properly treated. Therefore, several green companies have started to emerge to provide green products, although not all companies can produce environmentally friendly goods. This study was conducted to determine the effect of Environmental Knowledge and Green Advertising through Environmental Attitude on Green Purchase Intentions in green product supply stores in Bandung. Methodology: The method used is the quantitative method, with primary and secondary data. Data collection techniques through questionnaires to 100 respondents with probability sampling. The technique of data analysis used descriptive analysis and SEM (Amos). Finding: Based on structure equation model, it shows shows that Environmental Knowledge (EK) has a strong impact on the creation of Environmental Attitudes (EA), but still increases interest in buying environmentally friendly products (GPI). Green Advertising (GA) conducted by the company has a strong impact on increasing the formation of consumer behavior regarding environmental awareness but is still low in encouraging the purchase of environmentally friendly products (GPI). The formation of better consumer behavior towards the environment can increase the interest that is strong enough to buy environmentally friendly products. Conclusion: The increasing knowledge of consumers about a friendly environment and the continuous promotion efforts carried out by the company in producing environmentally friendly goods have a good effect on consumer behavior, although the implications have not yet given a strong impact on consumers in choosing environmentally friendly products.